Random Differential Equations in Scientific Computing - Neckel, Tobias; Rupp, Florian (De Gruyter Open, 2013)
The book offers a hollistic approach to the theory and numerics of random differential equations from an interdisciplinary and problem-centered point of view. In this interdisciplinary work, the authors examine state-of-the-art concepts of both dynamical systems and scientific computing
Keywords: Équations différentielles stochastiques; Ingénierie; Sciences; Dynamisches System; Engineering; MATHEMATICS / General; Numerisches Verfahren; Science; Stochastische Differentialgleichung; Zufällige Differentialgleichung; Engineering -- Data processing; Science -- Data processing; Stochastic differential equations -- Data processing; Electronic books